2018
DOI: 10.3791/56771
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Behavioral and Reproductive Consequences of Embryonic Exposure to Low-dose Toxicants

Abstract: Bisphenols, such as bisphenol A (BPA) and bisphenol S (BPS) are polymerizing agents widely used in the production of plastics and numerous everyday-use products. Based on their chemical structure and estradiol-like biological properties, they have been classified as endocrine disrupting compounds (EDC). Long-term exposure to EDCs, even at low doses, has been linked to various health defects including cancer, behavioral disorders and infertility, with greater vulnerability indicated during early developmental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The life cycle of C. elegans is around 3 days, and thus, 3-day-exposure is considered as long-term exposure that can be used in toxicological studies . Synchronized L1 wild-type N2 larvae were exposed to various concentrations of MG (0, 0.05, 0.1, 0.5, and 1 mM) in S-basal supplemented with E.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The life cycle of C. elegans is around 3 days, and thus, 3-day-exposure is considered as long-term exposure that can be used in toxicological studies . Synchronized L1 wild-type N2 larvae were exposed to various concentrations of MG (0, 0.05, 0.1, 0.5, and 1 mM) in S-basal supplemented with E.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The life cycle of C. elegans is around 3 days, and thus, 3-day-exposure is considered as long-term exposure that can be used in toxicological studies. 28 Synchronized L1 wild-type N2 larvae were exposed to various concentrations of MG (0, 0.05, 0.1, 0.5, and 1 mM) in S-basal supplemented with E. coli OP50 (1 × 10 10 CFU/mL) for 72 h at 20 °C until the larvae reached adult stage (day-0 adult). After washing thrice with M9 buffer, day-0 adult worms were transferred onto clean NGM plates and adapted for 60 s. The number of body bends of C. elegans was determined within 20 s on an NGM plate without food.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Recently we reported that chronic low-dose di-(2-ethylhexyl) phthatlate (DEHP) and nonylphenol (NP) has nonmonotonic estrogenic effects in mouse reproduction (Cha et al, 2017, 2018). The last few decades, most of the studies on EDCs have been based on the pharmacological dogma, that EDCs dose are poisonous (Vandenberg et al, 2012) and toxic (Vandenberg et al, 2012; Mersha et al, 2018; van der Weijden et al, 2018). Nowadays, EDCs are challenged in the view of physiological responses and reproductive tract disorders concerned with dose exposure and periods (Huang & Li, 2014; Mersha et al, 2018; van der Weijden et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The last few decades, most of the studies on EDCs have been based on the pharmacological dogma, that EDCs dose are poisonous (Vandenberg et al, 2012) and toxic (Vandenberg et al, 2012; Mersha et al, 2018; van der Weijden et al, 2018). Nowadays, EDCs are challenged in the view of physiological responses and reproductive tract disorders concerned with dose exposure and periods (Huang & Li, 2014; Mersha et al, 2018; van der Weijden et al, 2018). For example, low-dose expose studies have been done in behavior, Sobolewski et al 2014; Rebuli et al, 2015), obesity (Brulport et al, 2017), metabolism (Casals-Casas & Desvergne, 2011), and others (Casals-Casas & Desvergne, 2011; Zama & Uzumcu, 2013).…”
Section: Introductionmentioning
confidence: 99%